Nurturing Environmentally Responsible Practices Using Top Management Role on Effective Training and Supplier Orientation to Promote Green Logistics Management Practices - Sarpong, Kwame Owusu; Tuo, Gladys; Annan, Simon; Adu-Aboagye, Augustine (International Journal of Supply Chain and Logistics, 2024)
Purpose: This study investigated top management role on effective environmental training, using supplier environmental orientation to promote green logistics management practices. This was a deductive study since the positivist worldview was used to address the query about the relationship between variables. Methodology: The study used a quantitative method, which is consistent with the paradigm that was chosen. Data from the study population, which included Ghanaian manufacturing, agriculture, mining, and extraction companies, was gathered through questionnaires. The target population's size was ascertained using the Ghana Revenue Authority (GRA) database. The scientists used the Krejcie and Morgan (1970) sample size estimation table. Given the above, a sample size of 300 firms was selected from a total of 1178 respondents. The inclusion of descriptive statistics, such as Mean (x̄) and Standard Deviation (SD), contributes to a comprehensive understanding of the data. The application of SPSS software, version 25, for data analysis underscores a commitment to using reputable tools in the research process. Findings: The conclusion drawn from the results yielded robust reputable evidence in support of the positive relationship between environmental training and green logistics management practices. Unique Contribution to Theory, Policy, and Practice: Management should prioritize partnerships with suppliers who align with sustainable practices and contribute to the adoption of green logistics management practices within the supply chain.